2020
DOI: 10.1155/2020/5152646
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation Techniques of Coalbed Methane Reservoirs

Abstract: Coalbed methane (CBM) plays an important role in securing world energy supply and transiting electricity generation from fossil fuel to renewables. CBM reservoirs are generally very tight and require effective stimulation to achieve economic extraction. In recent years, an increasing number of coal seam stimulation techniques were developed, but selecting the most suitable stimulation technique for a particular CBM reservoir condition is becoming increasingly challenging. Therefore, it is deemed very i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 101 publications
0
24
0
Order By: Relevance
“…The techniques used in CBM stimulation can be categorized into three classes [37]: (i) mechanical stimulation, which includes hydraulic fracturing technique and formation blasting; (ii) thermal stimulation, such as using the cryogenic liquid nitrogen and heating, which intends to increase the rate of methane desorption, deteriorate the integrity of coal body, and weaken the mechanical strength of the coal as a result of temperature effect, which in turns lead to an improvement of permeability; (iii) chemical stimulation, such as acidification and microbial stimulation techniques, which focus mainly on dissolving the minerals in the coal to alter the porosity and enhance permeability.…”
Section: Coal Seam Stimulation Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…The techniques used in CBM stimulation can be categorized into three classes [37]: (i) mechanical stimulation, which includes hydraulic fracturing technique and formation blasting; (ii) thermal stimulation, such as using the cryogenic liquid nitrogen and heating, which intends to increase the rate of methane desorption, deteriorate the integrity of coal body, and weaken the mechanical strength of the coal as a result of temperature effect, which in turns lead to an improvement of permeability; (iii) chemical stimulation, such as acidification and microbial stimulation techniques, which focus mainly on dissolving the minerals in the coal to alter the porosity and enhance permeability.…”
Section: Coal Seam Stimulation Techniquesmentioning
confidence: 99%
“…Presently, hydraulic fracturing has become a standard stimulation method for tight oil and gas reservoirs. There is a challenge associated with such a stimulation technique, that is, the permeability of the coal reaches a peak value just after the fracturing process, but then the gas recovery declines as a result of the closure of the initiated fracture [37]. Thus, different improved hydraulic fracturing techniques have been proposed to overcome the problem, such as a graded particle injection and pulse hydraulic fracturing [39][40][41][42].…”
Section: Hydraulic Fracturingmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng et al [7][8][9], Lu et al [10], Feng and Kang [11] Wang et al [12], etc. have studied preextraction coal seam permeability enhancement after coal mine underground hydraulic slotting, and practices have shown that this technology can quickly and extensively enhance the coal seam permeability and the preextraction effect, laying a foundation for quickly eliminating the danger of gas outburst [13,14].…”
Section: Introductionmentioning
confidence: 99%